Teaching and Training Medical Students at the Midst of COVID-19 Pandemic: Unanswered Questions and the Way Forward - Shrestha, Shrijana (Journal of Nepal Health Research Council, 2020)
Medical doctors are the frontline workers in tackling any pandemics but ironically the medical students, especially the undergraduate medical students, who are the doctors in making, are being exempted from the lifetime experience of the current COVID-19 pandemic in most medical schools. In view of preventing the disease spread and maintaining social distancing the educational institutes including medical schools are closed in most countries struggling with the current pandemic. The decision is based on some evidences showing that the lockdown is one of the important tools to decrease transmission rates, delay the doubling time and flatten the curve. Unlike many other subjects and specialty, medicine has to be taught on patients and in the hospital setting. In this context there are several unanswered questions regarding the teaching and training of undergraduate medical students and the most important question being what is the best approach without compromising the safety as well as educational objectives and without overburdening the system? This article discusses some of these issues. Keyword: COVID-19; medical education; pandemic